1988
DOI: 10.1007/bf01324234
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a back care and light duty health promotion program in a hospital setting

Abstract: Back injuries are a common and expensive problem in industry in terms of both direct and indirect costs. A dramatic increase in the costs of workers' compensation for work-related back injuries occurred from 1981-1985 in a hospital setting. During this five-year period, costs of back injuries rose from $36,384 to $272,751, a 750% increase, and the incidence per thousand employees rose from 21 in 1981 to 33 in 1985. A back care education program was instituted by the Physical Therapy Department and Employee Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The content of diVerent training interventions included body mechanics, lifting technique, body posture, biomechanics, anatomy, pain management, ergonomic analysis, and job or work technique. Eight of these training programmes also included exercise training (Ryden et al 1988, Wollenberg 1989, Feldstein et al 1990, 1993, Guo et al 1992, Daltroy et al 1993, Lagerstrom et al 1998), but always as part of a larger training eVort. Seven of the studies used a randomized design (Carlton 1987, Dortch and Trombly 1990, McCauley 1990, Guo et al 1992, Daltroy et al 1993, Scopa 1993.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The content of diVerent training interventions included body mechanics, lifting technique, body posture, biomechanics, anatomy, pain management, ergonomic analysis, and job or work technique. Eight of these training programmes also included exercise training (Ryden et al 1988, Wollenberg 1989, Feldstein et al 1990, 1993, Guo et al 1992, Daltroy et al 1993, Lagerstrom et al 1998), but always as part of a larger training eVort. Seven of the studies used a randomized design (Carlton 1987, Dortch and Trombly 1990, McCauley 1990, Guo et al 1992, Daltroy et al 1993, Scopa 1993.…”
Section: Resultsmentioning
confidence: 97%
“…body mechanics varied by group). Ryden et al (1988) did not report on data collected after the intervention, so the eVects of the training could not be determined. Table 5 shows the 10 studies where new tools or technologies were the only interventions.…”
Section: Nonementioning
confidence: 95%
See 1 more Smart Citation
“…Interventions specific to work organizational factors including implementing modified return-to-work programs (Ryden, Molgaard, & Bobbitt, 1988) and re-training management to accept and accommodate workers with low back pain (Frank et al, 1996;Kaplansky, Wei, & Reecer, 1998) have also been suggested. In their literature review, Shannon, Mayr, and Haines (1997) identified empowerment of the work force, long-term commitment of the work force and good relations between management and workers to be important characteristics for reducing injury rates.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial reductions in disability for work-related injuries have been noted by the authors "with a wide range of specific workplace programs, nearly all of which have emphasized offering temporarily modified duties". Workplace intervention 'packages' that have been tested and reported repeatedly include 'comprehensive disability management', in which appropriately modified work is offered according to the injured worker's clinically or functionally assessed physical capacity (36)(37)(38)(39), sympathetic communication with the worker and nonadversarial handling of workers' compensation claims (40) and a mixture of approaches (41). Of special note is the repeated theme in these studies that a "supportive workplace response to injury needs to start when the pain is first reported; an individualized and accommodative approach to return to work should follow promptly" (32).…”
Section: Reducing Disability In Chronic Painmentioning
confidence: 99%